A review: characteristics and prevalence of psychrotolerant food spoilage bacteria in chill-stored meat, milk and fish - Suzita Ramli (Tanjung Malim, 2023)
A review: characteristics and prevalence of psychrotolerant food spoilage bacteria in chill-stored meat, milk and fish by Suzita Ramli